Sea Anemones Responding to Sex Hormones, Oxybenzone, and Benzyl Butyl Phthalate: Transcriptional Profiling and in Silico Modelling Provide Clues to Decipher Endocrine Disruption in Cnidarians - Morgan, Michael B.; Ross, James; Ellwanger, Joseph; Phrommala, Rebecca Martin; Youngblood, Hannah; Qualley, Dominic; Williams, Jacob (Frontiers in Genetics, 2022)
Endocrine disruption is suspected in cnidarians, but questions remain how occurs. Steroid sex hormones are detected in corals and sea anemones even though these animals do not have estrogen receptors and their repertoire of steroidogenic enzymes appears to be incomplete. Pathways associated with sex hormone biosynthesis and sterol signaling are an understudied area in cnidarian biology. The objective of this study was to identify a suite of genes that can be linked to exposure of endocrine disruptors. Exaiptasia diaphana were exposed to nominal 20ppb concentrations of estradiol (E2), testosterone (T), cholesterol, oxybenzone (BP-3), or benzyl butyl phthalate (BBP) for 4 hrs. Eleven genes of interest (GOIs) were chosen from a previously generated EST library. The GOIs are 17β-hydroxysteroid dehydrogenases type 14 (17β HSD14) and type 12 (17β HSD12), Niemann-Pick C type 2 (NPC2), Equistatin (EI), Complement component C3 (C3), Cathepsin L (CTSL), Patched domain-containing protein 3 (PTCH3), Smoothened (SMO), Desert Hedgehog (DHH), Zinc finger protein GLI2 (GLI2), and Vitellogenin (VTG). These GOIs were selected because of functional associations with steroid hormone biosynthesis; cholesterol binding/transport; immunity; phagocytosis; or Hedgehog signaling. Quantitative Real-Time PCR quantified expression of GOIs. In silico modelling utilized protein structures from Protein Data Bank as well as creating protein structures with SWISS-MODEL. Results show transcription of steroidogenic enzymes, and cholesterol binding/transport proteins have similar transcription profiles for E2, T, and cholesterol treatments, but different profiles when BP-3 or BBP is present. C3 expression can differentiate between exposures to BP-3 versus BBP as well as exposure to cholesterol versus sex hormones. In silico modelling revealed all ligands (E2, T, cholesterol, BBP, and BP-3) have favorable binding affinities with 17β HSD14, 17β HSD12, NPC2, SMO, and PTCH proteins. VTG expression was down-regulated in the sterol treatments but up-regulated in BP-3 and BBP treatments. In summary, these eleven GOIs collectively generate unique transcriptional profiles capable of discriminating between the five chemical exposures used in this investigation. This suite of GOIs are candidate biomarkers for detecting transcriptional changes in steroidogenesis, gametogenesis, sterol transport, and Hedgehog signaling. Detection of disruptions in these pathways offers new insight into endocrine disruption in cnidarians.